MODIFIABLE RISK FACTORS OF PREDIABETES - Khatri Sapkota, Niraj (Innovare Journal of Medical Sciences, 2017)
The presence of prediabetes risk is independently associated with expanded waist circumference or obesity, or investigated laboratory value of lowÂ high-density-lipoprotein-cholesterol levels, high triglycerides (dyslipidemia), or measured persistently raised blood pressure (hypertension) andÂ other miscellaneous factors such as eating and drinking habit. Association is stronger in male as compared to female, but abdominal obesity hasÂ stringent hold in both sexes to cause prediabetes. Recommendation has to be made on the basis of relative association to prevent or delay the onset ofÂ prediabetes to overt Type 2 diabetes; therefore, modifiable factors' recognition and applicatory improvement for the same are necessary. This reviewÂ attempts to recognize in short of applicable relevant modifiable risk factors of prediabetes.